A new cytotoxic 12-membered macrolactone from the endophytic fungus Exserohilum rostratum LPC-001. Issue 11 (2nd November 2018) - Lin, Peng-Cheng; Wu, Yu-Zhuo; Bao, Ting-Wen; Wang, Ya-Nan; Shang, Xiao-Ya; Lin, Sheng
Abstract: A new oxacyclododecindione-type macrolactone, (13 R, 14 S, 15 R )-13-hydroxy-14-deoxyoxacyclododecindione (1 ), has been obtained from the solid cultures of the fungus Exserohilum rostratum, a fungal strain endophytic in Gymnadenia conopsea . Its structure, including the absolute configuration, was extensively established by 1D and 2D NMR data, the modified Mosher method, and a combination of experimental and theoretically calculated electronic circular dichroism (ECD) spectra. Compound1 showed weak selective cytotoxicity against the A549 lung cell line with an IC50 value of 9.2 µM.